The Influence of Enterprise Resource Planning (ERP) Implementation System on Company Performance Mediated by Organizational Capabilities - Defriko Gusma Putra; Rita Rahayu; Anne Putri (Journal of Accounting and Investment, 2021)
Research aims: This study aims to examine the effect of Enterprise Resource Planning (ERP) system implementation on company performance with organizational capabilities as a mediating variable.Design/Methodology/Approach: This research is a quantitative study using 117 samples of manufacturing companies listed on the IDX from 2013 to 2018. Analysis and testing in this study employed SEM-PLS to test the effect of Enterprise Resource Planning (ERP) system implementation on company performance with organizational capabilities as a mediating variable.Research findings: The results showed that the ERP system's implementation had a significant positive effect on company performance and organizational capabilities. Organizational capabilities also had a significant positive effect on company performance. Besides, it was found that organizational capabilities mediated the relationship between ERP system implementation and company performance.Theoretical contribution/Originality: This study utilized a cybernetics approach theory, Resource-Based View (RBV) theory, and organizational capabilities theory to investigate the mediating role of organizational capabilities in increasing the impact of ERP systems on company performance.Practitioner/Policy implication: This study provides evidence that ERP implementation makes an integrated operating system and can increase organizational capabilities by utilizing existing resources, and ultimately will also increase company performance.Research limitation/Implication: In this research, it is challenging to find organizational capability measures, such as marketing capability and process improvement. This study only used one intervening variable so that the information obtained from the results is still limited.